2012
DOI: 10.4021/jmc874w
|View full text |Cite
|
Sign up to set email alerts
|

A Potentially Fatal Complication of Biliary Stent Migration

Abstract: A 77-year-old woman undergoing chemotherapy for mantle cell lymphoma presented with acute lower abdominal pain and pneumoperitoneum. Emergency laparotomy revealed a perforation of the sigmoid colon due to a migrated biliary stent requiring sigmoid resection and colostomy formation. This case highlights the potential complications that may arise from migrated biliary stents and discusses the management options in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Benign biliary strictures were associated with a higher risk of migration than malignant biliary strictures [ 4 ]. Thus, patients affected by a benign disease exhibited a higher frequency of migration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benign biliary strictures were associated with a higher risk of migration than malignant biliary strictures [ 4 ]. Thus, patients affected by a benign disease exhibited a higher frequency of migration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature have also reported perforations in the liver, sigmoid colon, caecum, and pancreas [ 3 , 10 ]. A literature review performed in 2007 described 11 cases in which migrating stents caused colonic perforation [ 7 ]. A number of studies have also reported that bowel wall penetration is associated with complications such as perforation of the small bowel, sigmoid diverticular perforation, and enteroenteric fistula formation [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic placement of biliary stents is a well-established, safe and minimally invasive procedure, commonly used in the treatment of a wide variety of biliary disorders 1. Biliary stent migration is an unusual event2 occurring in up to 10% of patients 3.…”
Section: Descriptionmentioning
confidence: 99%